Child- and family-focused cognitive-behavioral therapy for pediatric bipolar disorder: Development and preliminary results - Pavuluri, M; Graczyk, P; Henry, D; Carbray, J; Heidenreich, J; Miklowitz, D (2004)
Objective: To describe child- and family-focused cognitive-behavioral therapy (CFF-CBT), a new developmentally sensitive psychosocial intervention for pediatric bipolar disorder (PBD) that is intended for use along with medication. CFF-CBT integrates principles of family-focused therapy with those of CBT. The theoretical framework is based on (1) the specific problems of children and families coping with bipolar disorder, (2) a biological theory of excessive reactivity, and (3) the role of environmental stressors in outcome. CFF-CBT actively engages parents and children over 12 hour-long sessions. Method: An exploratory investigation was conducted to determine the feasibility of CFF-CBT. Participants included 34 patients with PBD (mean age 11.33 years, SD = 3.06) who were treated with CFF-CBT plus medication in a specialty clinic. Treatment integrity, adherence, and parent satisfaction were assessed. Symptom severity and functioning were evaluated before and after treatment using the severity scales of the Clinical Global Impression Scales for Bipolar Disorder (CGI-BP) and the Children's Global Assessment Scale (CGAS) respectively. Results: On completion of therapy, patients with PBD showed significant reductions in severity scores on all CGI-BP scales and significantly higher CGAS scores compared to pretreatment results. High levels of treatment integrity, adherence, and satisfaction were achieved. Conclusions: CFF-CBT has a strong theoretical and conceptual foundation and represents a promising approach to the treatment of PBD. Preliminary results support the potential feasibility of the intervention.